OPTIMIZING VAKOG AS HUMAN SENSES IN TEACHING ENGLISH FOR YOUNG LEARNERS - Prabowo, Jumbuh (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2015)
Teaching English for young learners always gets more attention. It is because young learners are very unique. They have many characters which can change rapidly in one time. Sometimes, they display an enthusiasm for learning and a curiosity about the world around them. They also have a need for individual attention and approval from the teacher. They are keen to talk about themselves, and respond well to learning that uses themselves and their own lives as main topics in the classroom. However, they also have a limited attention span. They can easily get bored, losing interest after ten minutes if the activities are not extremely engaging.Considering those characters, there should be good ways how to treat children in delivering materials. One of ways is by exposing and utilizing childrenâs senses. The senses are Visual, Auditory, Kinesthetic, Olfactory, and Gustatory (VAKOG). It will be very useful because a teacher not only gives something to be seen but also invites them to get involved mentally and physically. In this case, the teacher will prepare a set of teaching material where this material has very tight relationship with activities done in class. For instance, when teacher will teach part of body, she or he will prepare some pictures, songs, games, and other activities related to bodyâs part. These are intended to strengthen childrenâs knowledge.